Effectiveness of Thymoquinone and Fluoridated Bioactive Glass/Nano-Oxide Contained Dentifrices on Abrasion and Dentine Tubules Occlusion: An Ex Vivo Study - Anthoney, Daud; Zahid, Shahreen; Khalid, Hina; Khurshid, Zohaib; Shah, Asma Tufail; Chaudhry, Aqif Anwar; Khan, Abdul Samad (European Journal of Dentistry, 2020)
Objectives Dentin hypersensitivity (DH) is mainly due to the loss and replenishment of minerals from tooth structure, where the lost minerals can be rehabilitated with a biomimetic approach. The objectives were to determine the relative dentin abrasivity (RDA) of experimental (EXT) dentifrices and to determine the efficacy to occlude dentinal tubules.Materials and Methods Experimental dentifrices contained nano-fluoridated bioactive glass (n-FBG: 1.5 wt.% [EXT-A], 2.5 wt.% [EXT-B], and 3.5 wt.% [EXT-C]), nano-zinc oxide (n-ZnO), and thymoquinone as active agents. Bovine dentin blocks were subjected to brushing treatments as per groups, that is, distilled water; commercial dentifrice (control, CT); EXT toothpastes; and EXT-D without active agents. Samples were tested for three-dimensional (3D) abrasion analysis according to ISO-11609:2010 (International Organization for Standardization [ISO]). The roughness average (Ra), RDA, surface topography, and elemental compositions were investigated.Statistical Analysis One-way analysis of variance (ANOVA) with post-hoc Tukey’s and Tamhane’s test was performed for characterizations using Statistical Package for the Social Sciences (SPSS) version 21. The result was considered significant with p-value ≤ 0.05.Results Comparisons of Ra differed significantly between all groups with p < 0.05 except CT and EXT-A. The RDA values of EXT-A, EXT-B, and EXT-C were calculated as 74.04, 84.26, and 116.24, respectively, which were well within the acceptable limit set by international standards. All n-FBG containing dentifrices demonstrated uniform occlusion of dentinal tubules; however, highly concentrated EXT dentifrices showed more occlusion.Conclusions Acceptable range of RDA and superior occlusion of tubules by novel dentifrices suggest that it may be recommended for treating DH.
Keywords: dentin sensitivity; dentifrices; abrasion; bioactive glasses; zinc oxide; tooth remineralization